2017
DOI: 10.1002/wcms.1347
|View full text |Cite
|
Sign up to set email alerts
|

Water models for biomolecular simulations

Abstract: Modern simulation and modeling approaches to investigation of biomolecular structure and function rely heavily on a variety of methods—water models—to approximate the influence of solvent. We give a brief overview of several distinct classes of available water models, with the emphasis on the conceptual basis at each level of approximation. The main focus is on classes of models most widely used in atomistic simulations, including popular implicit and explicit solvent models. Among the latter, nonpolarizable N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
237
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(241 citation statements)
references
References 476 publications
(820 reference statements)
4
237
0
Order By: Relevance
“…SHAKE or SETTLE), are used in combination for increased computational efficiency. However, more complex, and presumably more accurate, models such as TIP4P-Ew (Horn et al 2004) are being increasingly utilized in biomolecular simulations (Onufriev & Izadi, 2018). Ion parameters are intimately tied to water models (Joung & Cheatham III, 2008), and all the force fields representing system components should be compatible with one another in order to provide an accurate balance of protein-water-lipid-ion interactions that allows for a complete description of ion permeation and channel gating.…”
Section: Figure 2 a Typical Ion Channel All-atom MD Simulation Systementioning
confidence: 99%
“…SHAKE or SETTLE), are used in combination for increased computational efficiency. However, more complex, and presumably more accurate, models such as TIP4P-Ew (Horn et al 2004) are being increasingly utilized in biomolecular simulations (Onufriev & Izadi, 2018). Ion parameters are intimately tied to water models (Joung & Cheatham III, 2008), and all the force fields representing system components should be compatible with one another in order to provide an accurate balance of protein-water-lipid-ion interactions that allows for a complete description of ion permeation and channel gating.…”
Section: Figure 2 a Typical Ion Channel All-atom MD Simulation Systementioning
confidence: 99%
“…Apart from the force field, a water model also needs to be selected to model the solvent; a wide range of models exist for this purpose. Here we are using the common TIP3P model, which is an example of a 'three-site model' -socalled because the molecule is modeled using three points, corresponding to the three atoms of water (Four-and five-site models include additional 'dummy atoms' representing the negative charges of the lone pairs of the oxygen atom) (22).…”
Section: Rename Output To 'Ligand (Pdb)'mentioning
confidence: 99%
“…Parametrization of FFs is considered essential, and various methods and variations of parameters are still being developed actively. For example, the water molecule is the most active target of parameterization . A study regarding the SPC/E water model reported that a 1% increase in the length of the OH bond led to accurate reproducibility of the translational and rotational diffusion of pure water and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the water molecule is the most active target of parameterization. [6] A study regarding the SPC/E water model [7] reported that a 1% increase in the length of the OH bond led to accurate reproducibility of the translational and rotational diffusion of pure water and proteins. This newly developed model was named SPC/E b .…”
Section: Introductionmentioning
confidence: 99%